2020
DOI: 10.3390/ma13245762
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Properties of Oil-in-Water Emulsion with Carbon Nanocapsule Additives

Abstract: An experimental investigation was performed on the coefficients of friction (COFs) and wear properties of pure water and oil-in-water (O/W) working fluids containing carbon nanocapsules (CNCs) with concentrations ranging from 0 to 1.0 wt.%. For the O/W working fluid, the ratio of oil to water was set as 6%. It was shown that for the water working fluid, the COF decreased by around 20% as the CNC content increased from 0 to 1.0 wt.%. In contrast, the wear volume increased by 50% as the CNC addition increased fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…For instance, Wu prepared water‐based nano‐lubricants using TiO 2 nanoparticles and evaluated their application in hot steel rolling, and the result demonstrated that TiO 2 nanoparticles had significant effect on polishing of the work surface roll 12,13 . Various carbon nanoparticles are also applied to prepare nanofluid used for cutting, such as graphite, diamond particles, carbon spheres, carbon nanocapsules, C60, carbon nanotubes, and so on 14–17 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Wu prepared water‐based nano‐lubricants using TiO 2 nanoparticles and evaluated their application in hot steel rolling, and the result demonstrated that TiO 2 nanoparticles had significant effect on polishing of the work surface roll 12,13 . Various carbon nanoparticles are also applied to prepare nanofluid used for cutting, such as graphite, diamond particles, carbon spheres, carbon nanocapsules, C60, carbon nanotubes, and so on 14–17 …”
Section: Introductionmentioning
confidence: 99%
“…10,11 For instance, Wu prepared water-based nano-lubricants using TiO 2 nanoparticles and evaluated their application in hot steel rolling, and the result demonstrated that TiO 2 nanoparticles had significant effect on polishing of the work surface roll. 12,13 Various carbon nanoparticles are also applied to prepare nanofluid used for cutting, such as graphite, diamond particles, carbon spheres, carbon nanocapsules, C60, carbon nanotubes, and so on [14][15][16][17] Nanotubes consisted of monolayer or multi-layer graphite sheets curled around the center at certain angles, this structure was first proved by Iijima in 1991. 18 As a kind of lubricant additive, multi-walled carbon nanotubes (MWCNTs) or their chemical modifiers can significantly improve the tribological properties of the base fluid according to the research of Qian et al [19][20][21] Peng used concentrated acid to conduct the oxidation treatment for MWCNTs and adopted Four-Ball method to measure the tribological properties of water-based lubricant containing MWCNTs modifications, and the result indicated that the extreme load of the lubricant was 3 $ 7 times higher than that of pure water.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on water-based or watercontaining fluids have been conducted. For example in [23][24][25] experimental investigations were carried out with mineral-oil, pure water and oil-in-water working fluids containing carbon nanocapsules. In [26] synthetic polymers are examined regarding their surface interactions and in [27] the coefficient of friction of a water-based fluid is determined for different shear rates.…”
Section: Introductionmentioning
confidence: 99%